WebSphere Business Integration Server Express : the express route to business integration - Moore, Bill; Buset, Knut Inge; Higgins, Dennis; Palmieri, Wagner; Pedersen, Mads; Wende, Joerg; Wong, Alison (IBM redbooks., 2005)
This IBM Redbooks publication provides guidance for IT specialists and architects who are implementing enterprise application integration (EAI) projects for small and medium businesses. It provides best practices and advice for all levels of an EAI solution, including design, implementation and deployment using the WebSphere Business Integration Server Express. This book discusses types of application integration, such as data level (information) integration, application logic (API) integration and process integration, and considers different EAI architectures such as brokers or point-to-point integration. It provides guidance for analyzing and understanding requirements such as real time, nearly real time and delayed integration and describes how to architect a manageable solution. A sample application will be implemented which focuses on the development of a practical EAI example for developers using WebSphere Business Integration Server Express.